MISP regulates the IQGAP1/Cdc42 complex to collectively orchestrate spindle orientation and mitotic progression - Vodicska, Barbara; Cerikan, Berati; Schiebel, Elmar; Hoffmann, Ingrid (Scientific reports, 2018)
Precise mitotic spindle orientation is essential for both cell fate and tissue organization while defects in this process are associated with tumorigenesis and other diseases. In most animal cell types, the dynein motor complex is anchored at the cell cortex and exerts pulling forces on astral microtubules to position the spindle. The actin-binding protein MISP controls spindle orientation and mitotic progression in human cells. However, the exact underlying mechanism remains to be elucidated. Here we report that MISP interacts with the multidomain scaffolding protein IQGAP1. We further show that MISP binds to the active form of Cdc42 through IQGAP1. Depletion of MISP promotes increased accumulation of IQGAP1 at the cell cortex and a decrease in its Cdc42-binding capacity leading to reduced active Cdc42 levels. Interestingly, overexpression of IQGAP1 can rescue mitotic defects caused by MISP downregulation including spindle misorientation, loss of astral microtubules and prolonged mitosis and also restores active Cdc42 levels. Importantly, we find that IQGAP1 acts downsteam of MISP in regulating astral microtubule dynamics and the localization of the dynactin subunit p150glued that is crucial for proper spindle positioning. We propose that MISP regulates IQGAP1 and Cdc42 to ensure proper mitotic progression and correct spindle orientation.
Gesehen am 25.03.2019